(untitled) (African Human Rights Yearbook / Annuaire Africain des Droits de l’Homme, 2023)
This article examines the mechanisms and instruments employed by the three main regional African human rights bodies – the African Commission and African Court on Human and Peoples’ Rights and the African Children’s Rights Committee – to monitor compliance with their decisions and judgments. Based on the assumption that second-order compliance monitoring contributes to greater effectiveness of human rights institutions and increased compliance with their pronouncements, we discuss the monitoring tools used by the institutions themselves as well as the roles of political monitoring and monitoring by civil society. Based on a stock-taking exercise we find that all three African human rights bodies still have much room for improving both the quantity and the quality of their monitoring instruments and processes. Acknowledging that the three bodies may to some extent be legally and politically constrained with respect to the use of some of these, and recognising that the AU’s political organs mostly abstain from exercising the second-order compliance monitoring functions assigned to them, the article argues that civil society plays a critical role in contributing to such monitoring, a role that should be expanded upon and researched further.